Combined encryption method for CAN bus data based on periodic coupled processing - Wutao QIN; Peng WANG; Yufeng LI (Tongxin xuebao)
In the intelligent connected age, CAN bus transmission faces the urgent demand of light weighted security encryption.Based on this, a fast response and high security CAN bus data encryption method was proposed.Since the 64 bit CAN packets were sent periodically, an online-offline block encryption algorithm coupled with message transmission cycle was proposed.In offline phase, the dynamic session key was generated by using advanced encryption standard.In online phase, the dynamic session key was used to quickly respond to encryption and decryption requests.The online computation delay was greatly reduced by the pre-encryption computation in offline phase, which helped achieving low latency and lightweight computation.At the same time, the ciphertext policy attribute based encryption was used to encrypt the block cipher.The access control policy made by the data sending OBU ensures that only the target OBU can decrypt the block cipher, so as to achieve targeted encryption.